Innovative Applications of Environmental Monitoring using Medical Physics-Based Radiation Sensors - Saadun, Zainab Haider Musa; Makki, Baneen Hazim Aziz; Rahi, Fatima Hashim Matar; Reda, Hussein Falah Musa; Aziz, Hawraa Abbas Alwan (American Journal of Botany and Bioengineering, 2025)
An increase in human sources of radioactivity in the environment may lead to a significantly higher background of natural or artificial ionizing radiation. Even if levels are not generally hazardous, the uncertainties for cancer and hereditary risks in moderate and high doses are not yet quantifiable. In addition, a lot of intentional or unintentional accidents involving a source of ionizing radiation lead to local contamination or a terrestrial contamination plume. Immediately after the event, the authorities working on a tragedy have to deal with many problems, including the radiological characterization of the region, the mapping of the contamination levels, the classification of the areas in terms of intervention measures for protecting the population, etc. The aim of this work package is to remove these problems and make the identification of contamination as short as possible, in order to avoid panic and chaos. For this purpose, it is possible to develop a radiation sensor based on the position sensing of scintillation light in a coplanar grid (CPG) detector, where the scintillation process is carried out in a sodium iodide (NaI) crystal scintillator. The secondary ionic scintillation threshold is lower than that from scintillation light. This way, it is possible to have a portable detector, which may be a complement to the present ones, especially those allowing these problems and tasks to be performed silently and in a completely remote way. The high sensitivity of a CPG detector for the electromagnetic radiation produced by the scintillation permits the localization of the scintillation activity and also generates an image that allows a quick overview of the extension of the contaminations, as well as the precise localization of hot spots.